2016
DOI: 10.1016/j.jsr.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lead time of verbal collision warning messages on driving behavior in connected vehicle settings

Abstract: The findings have implications for the design of collision warning systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…A connected environment allows exchange of traffic information with roadside units and/or other vehicles, which can warn drivers about hazardous situations within or out of sights and thereby reduce crash risk. For instance, Wan et al (2016) analysed the effects of lead time of verbal collision warning messages on car-following behaviour and reported that gradual braking and shorter response time of drivers when the lead time was between 5 to 8 s. Chrysler et al (2015) concluded that drivers identified potential threat sooner in a connected environment compared to a traditional environment, resulting in shorter response times. Lin et al (2016) reported longer response times of drivers in a connected environment in hazardous conditions such as fog, which contrasts the findings of several past studies.…”
Section: Response Time In a Connected Environmentmentioning
confidence: 99%
“…A connected environment allows exchange of traffic information with roadside units and/or other vehicles, which can warn drivers about hazardous situations within or out of sights and thereby reduce crash risk. For instance, Wan et al (2016) analysed the effects of lead time of verbal collision warning messages on car-following behaviour and reported that gradual braking and shorter response time of drivers when the lead time was between 5 to 8 s. Chrysler et al (2015) concluded that drivers identified potential threat sooner in a connected environment compared to a traditional environment, resulting in shorter response times. Lin et al (2016) reported longer response times of drivers in a connected environment in hazardous conditions such as fog, which contrasts the findings of several past studies.…”
Section: Response Time In a Connected Environmentmentioning
confidence: 99%
“…As such, HRGC alerts should be designed considering these hazard levels and their effect on driver behavior and perception. Additional parameters of importance include vehicle lead time (26) and system reliability (27), which both must be considered for application in realistic driving settings.…”
Section: Ivaa Considerations For Hrgcs and Past Researchmentioning
confidence: 99%
“…Lead time is one such variable requiring evaluation, as it represents one of the first considerations when designing an IVAA, and should vary depending on the purpose of the display. Existing research on lead time selection points to varying lead times for safety applications, such as take-over requests [12] and forward collision warnings [13], further suggesting the need for an evaluation for HRGCs. Performance at HRGCs can also be considered as distinct from other automotive applications, as appropriate behavior at crossings also involves visually monitoring the crossing for a train and existing warning displays present at crossings.…”
Section: Introductionmentioning
confidence: 99%